The links between membrane actin assembly by mycobacterial phagosomes and phagosome maturation, macrophage activation and pathogen killing - Jordão, Maria Luísa Forte Marques, 1969- (2010)
Tese de doutoramento em Farmácia (Biologia e Genética Molecular), apresentada à Universidade de Lisboa através da Faculdade de Farmácia, 2008